2018
DOI: 10.3389/fphys.2018.01799
|View full text |Cite
|
Sign up to set email alerts
|

Review on Chamber-Specific Differences in Right and Left Heart Reactive Oxygen Species Handling

Abstract: Reactive oxygen species (ROS) exert signaling character (redox signaling), or damaging character (oxidative stress) on cardiac tissue depending on their concentration and/or reactivity. The steady state of ROS concentration is determined by the interplay between its production (mitochondrial, cytosolic, and sarcolemmal enzymes) and ROS defense enzymes (mitochondria, cytosol). Recent studies suggest that ROS regulation is different in the left and right ventricle of the heart, specifically by a different activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 131 publications
(154 reference statements)
2
27
0
Order By: Relevance
“…On the contrary, when Sirtuin-3 knockout mice were exposed to chronic hypoxia, they developed PH and RV hypertrophy that was indistinguishable from those in wildtype littermates [44]. Several studies demonstrated that LV and RV differ in the expression profiles of genes and proteins, suggesting that these differences may generate specific molecular patterns with relevance to their pathophysiology [13,15,16,33,36,43] and thus responses to therapies [4,11,23,45]. We speculate that the responsiveness of FHL-1 to stress signals could be influenced by other proteins that differ between LV and RV.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, when Sirtuin-3 knockout mice were exposed to chronic hypoxia, they developed PH and RV hypertrophy that was indistinguishable from those in wildtype littermates [44]. Several studies demonstrated that LV and RV differ in the expression profiles of genes and proteins, suggesting that these differences may generate specific molecular patterns with relevance to their pathophysiology [13,15,16,33,36,43] and thus responses to therapies [4,11,23,45]. We speculate that the responsiveness of FHL-1 to stress signals could be influenced by other proteins that differ between LV and RV.…”
Section: Discussionmentioning
confidence: 99%
“…This difference to LV tissue is due to a stronger induction of fibrosis, triggered by collagen III, lack of effect on cardiomyocytes and (Schluter et al, 2018) Rat, L-NAME, 4 weeks ROS in RV " (Schreckenberg et al, 2015) Wild-type and NOS2-deficient mice, PAB, 3 weeks…”
Section: Exercise-dependent Preconditioning Of the Rvmentioning
confidence: 99%
“…In the specific case of ACM, this hypothesis has not been tested yet, though it is tempting to speculate that metabolic and mitochondrial dysfunction can serve as substrates for electrical and structural changes in ACM patients. Especially since previous studies have indicated differences in mitochondrial metabolism between the left ventricle (LV) and right ventricle (RV) in the heart and ACM is regarded a (right) chamber specific disease (Schlüter et al, 2018). In this review, we describe the mitochondrial (patho)physiology, the link between mitochondrial dysfunction and development of cardiac arrhythmias and explore a potential relation between mitochondrial dysfunction and typical hallmarks of ACM.…”
Section: Introductionmentioning
confidence: 99%